What a curator needs to know – the development of professional museum work and the skills required in Danish museums 1964–2018. (3rd September 2019) - Jensen, Susanne Krogh
ABSTRACT: In this paper, I ask how the professional jurisdiction and the discourse on professional skills for Danish museum professionals have changed from 1964 to 2018. Based on empirical content analysis of job ads and on qualitative interviews with museum professionals, I track the professionalization of museum jobs mapping a development from the definition of a generic profession during the 1960s and 1970s, over the establishment of an academic managerial level during the 1980s and 1990s to a diversification and specialization since 2000. Analyzing the discourse on professionalism, I find an increasing focus on performativity and the definition of personal skills required of professionals, while standardized credentials have become less important.